Asexual proliferative seedling technology for Sargassum fusiforme constructed using tissue culture method - Guo, Lina; Pang, Guanfeng; Luo, Lin; Gao, Congquan; Chen, Binbin; Ma, Zengling (Frontiers in Marine Science, 2024)
The traditional method of sexual reproduction in Sargassum fusiforme can lead to difficulties in maintaining the stable inheritance of superior traits. However, technology for asexual proliferation of seedlings in seaweed tissue culture is not well-developed. Therefore, we established a tissue culture method to study, the effects of different parts of S. fusiforme, uniconazole (UIZ) concentrations, and culture methods on the regeneration of tissue-derived juveniles of S. fusiforme. The results showed that the optimal culture conditions were solid medium with modified Provassoli’s enriched seawater containing 3 μM UIZ for at least 17 days followed by transfer to liquid medium to induce rapid cell proliferation. These optimal conditions resulted in a callus-like/adventitious bud induction rate of 100%, callus-like/adventitious bud number per explant of 27.43 ± 4.57, and relative growth rate of 3.05 ± 0.27. The best plant parts for tissue culture were the filamentous holdfasts followed by the stem tip. In addition, UIZ treatment increased photosynthesis, resulting in soluble sugar and soluble protein contents of 30.47 mg·g-1 and 1.39 mg·g-1 of in the regenerated juveniles. Based on our results, S. fusiforme can be cultured using a tissue culture technique in which UIZ is added to a solid medium, followed by culture in liquid medium for proliferation. Sargassum fusiforme juveniles obtained using this technique can be cultured continuously until the next culture season and grow normally, providing a technical reference for indoor preservation and expansion of algal species.